Incidence of Japanese encephalitis virus among patients presenting with acute encephalitis syndrome in a tertiary care hospital, West Bengal, India - Roy, Arup; Saha, Poulami; Islam, Asraful; Saha, Rajdeep; Sengupta, Abhishek; Mondal, Arnab K.; Saha, Puranjay (International Journal Of Community Medicine And Public Health, 2021)
Background: Japanese encephalitis virus (JEV) is a flavivirus related to dengue, yellow fever and West Nile viruses, and is spread by mosquitoes. JEV is the main cause of viral encephalitis in many countries of Asia with an estimated 68000 clinical cases every year. Although symptomatic Japanese encephalitis (JE) is rare, the case-fatality rate among those with encephalitis can be as high as 30%. Permanent neurologic or psychiatric sequelae can occur in 30-50% of those with encephalitis. This study was conducted to find the incidence of JEV IgM in patients presenting with acute encephalitis syndrome (AES) in Raiganj govt. medical college and hospital, Uttar Dinajpur, West Bengal, India. Methods: Blood and CSF samples were collected from patients presenting with AES. IgM antibody capture ELISA was performed on the CSF and serum samples by JE virus MAC ELISA kit. Results: The overall prevalence of JEV IgM was 13.8%. Among the positive cases male comprised of 71.4% and female 28.5%. The most common age group affected was above 16 years of age. JEV prevalence was present throughout the year with high number of cases between the monsoon and post monsoon seasons. Conclusions: This study demonstrates the endemicity of JEV in Uttar Dinajpur district of West Bengal, India. As most of the JE cases are asymptomatic strengthening the existing surveillance system is required to find out the actual scenario of JEV in West Bengal. Control of vectors, early diagnosis and treatment, vaccinations are the key to decrease the morbidity and mortality caused by JEV.